Hadith Criticism: A Practical Guide to Determining the Authenticity of the Sunnah - Afifudin; Asep Mahfud; Engkos Kosasih; Irwan Abdurrohman; Muhammad Al Mighwar (al-Afkar, Journal For Islamic Studies, 2026)
Hadith Criticism (Naqd al-Ḥadīṡ) is an important discipline developed by scholars to examine and verify the authenticity of narrations claimed to originate from Prophet Muhammad (PBUH). Its main objective is to differentiate between Sahih (authentic) hadiths and Da'if (weak) or Mawdhu' (forged) hadiths. This research aims to analyze and compile the practical stages of Hadith Criticism so that it is easily understood by beginner students. By using a descriptive-analytical literature review method on the foundational books of Hadith science, this research summarizes the criticism process. This research shows that Hadith Criticism is an integrated, two-dimensional process. First, Sanad Criticism (Chain of Narration), where the Hadith must fulfill five main conditions (the chain is connected, the narrator is just ('ādil), ḍābiṭ (strong in memory), is not shādhdh (anomalous), and is not mu'allal (possessing a hidden defect)). Second, Matn Criticism (Hadith Content): Examining the conformity of the hadith's content with the Qur'an and established principles of Shari'ah. The conclusion of this research is that the systematic understanding and application of the Hadith Criticism methodology are fundamental prerequisites in Islamic studies. This research contributes by presenting this complex methodology as a step-by-step guide to enhance the students' ability to filter and accept the pure Sunnah of the Prophet.